2000
DOI: 10.1111/j.1469-8749.2000.tb00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth and subsequent mental health problems in children aged 4 to 13 years

Abstract: To test the hypothesis that children with suboptimal fetal growth have significantly poorer mental health outcomes than those with optimal growth, a population random sample survey of children aged 4 to 16 years in Western Australia in 1993 was conducted. The Child Behavior Checklist (Achenbach 1991a) and the Teacher Report Form (Achenbach 1991b) were used to define mental health morbidity. Survey data for 1775 children aged 4 to 13 years were available for linkage with original birth information. The percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 36 publications
(36 reference statements)
4
32
3
Order By: Relevance
“…An earlier study had reported more behavioral problems in very preterm SGA children (17), whereas other studies failed to confirm these findings (6,18). As regards ADHD, we found no significant difference between the SGA children and the con trols.…”
Section: Discussioncontrasting
confidence: 75%
“…An earlier study had reported more behavioral problems in very preterm SGA children (17), whereas other studies failed to confirm these findings (6,18). As regards ADHD, we found no significant difference between the SGA children and the con trols.…”
Section: Discussioncontrasting
confidence: 75%
“…Higher prevalence of moderate ID among male children has been reported, with males 1.6-1.9 times more likely to be classified with moderate ID than females (Croen, Grether, & Selvin, 2001;Drews, Yeargin-Allsopp, Decoufle, & Murphy, 1995;Richardson, Katz, & Koller, 1986), and these sex differences seem to increase with age up to 15 years (Wen, 1997). Factors that could play a role in sex differences for ID are X-linked conditions (Chelly & Mandel, 2001;Partington, Mowat, Einfeld, Tonge, & Turner, 2000;Tariverdian & Vogel, 2000), low birth weight and an association between low birth weight and low IQ in males (Matte, Bresnahan, Begg, & Susser, 2001;Zubrick et al, 2000), and maternal smoking, which has a proportionaly higher detrimental effect on males than females (Zaren, Lindmark, & Bakketeig, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that, in babies born with SGA, there are mild neurological, behavioral, emotional problems at various levels, and their cognitive scores and academic successes are lower when compared to children born with a normal birth weight according to gestational age. When the literature was analyzed, low birth weight was found to be related to problems such as attention deficit, ADHD, anxiety-depression, aggression, and disorders of mental state involving symptoms of both introversion and extroversion [20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, 10 th age academic success was lower in SGA cases, but there was no significant difference between them in terms of WISC-R results 22 . Zubrick SR et al 20 stated that a wider range of mental health problems was present (anxiety, depression, ADHD, and conduct disorder) in cases with low birth weights. In our study, similar to the literature 5,22,24,32 , the school success was found to be lower in the cases with SGA when compared to the control group (47.8% vs. 9.3%), and they were diagnosed with ADHD more frequently.…”
Section: Discussionmentioning
confidence: 99%